Financial feasibility of developing solar irrigation in Mali - Xie, Hua; Ringler, Claudia (International Food Policy Research Institute, 2023)
Mali is home to 22 million people, 12 million of whom live in rural areas and work mostly in agriculture. Although remarkable progress has been made, food insecurity still affects a large share of the population; during 2019-2021, the prevalence of undernourishment in the population was 10%, and in 2020 26% of children below the age of five were stunted.